PENGEMBANGAN MATERI AJAR TEKS NARASI BERMUATAN ECOLITERACY BERBASIS BLOG PADA SISWA KELAS VII SMP - Ida Sukowati (Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to: (a) describe the design of developing narrative text teaching materials with ecoliteracy content based on a class blog for seventh-grade students; (b) describe the validity of the developed product; and (c) describe user responses to the materials. This research employed a Research and Development (R&D) method using the Borg and Gall and Dick and Carey models, with a mixed-methods approach. Data were collected through observation, interviews, and questionnaires. Expert validation involved material and media experts. The results showed that the design included a teaching module and a class blog. Material expert validation reached 89.29% (highly feasible), and media expert validation reached 97.50% (highly feasible), with an overall average of 93.40% (highly feasible). Student responses to the needs analysis indicated 81.91%, and teacher responses indicated 100%. Therefore, the developed narrative text teaching materials with ecoliteracy content based on a class blog are highly feasible for use in Indonesian language learning in seventh grade.